Turbulent drag at the ice-ocean interface of Europa in simulations of rotating convection: implications for nonsynchronous rotation of the ice shell - Hay, HCFC; Fenty, I; Pappalardo, RT; Nakayama, Y (American Geophysical Union, 2023)
Europa's geologically scarred surface shows significant evidence that the ice shell may have rotated nonsynchronously in the past. The long-term spin state of the ice shell is controlled by the time-mean torques acting upon it. A torque that has not been previously considered is exerted due to drag from oceanic currents beneath the ice. We estimate this torque for the first time by performing global, nonhydrostatic, three-dimensional simulations of Europa's ocean, including nonlinear turbulent boundary layer drag at the seafloor and ice-ocean interface. Our simulations show that ocean dynamics, which manifest in alternating east-west jets, result in a net torque on the ice shell. The torque can act to either spin up or spin down the ice shell depending on the strength of convection, suggesting that a torque reversal can occur as Europa's interior thermally evolves. Scaling analysis indicates that an average jet speed of at least ∼1 cm s−1 is required for the ice-ocean torque to be comparable to the tidal torque acting to spin up the ice shell. Our results suggest that ocean currents may contribute to any nonsynchronous rotation of the ice shell. Consequently, Europa's present-day spin state may hold information about the dynamics of its subsurface ocean.